Nanomaterials and devices : processing and applications - Ray, S., of Indian Inst. of Tech., Roorkee (Trans Tech Publications, 2009)
The focus of this special collection was the applied aspects of nano-materials; with almost all of the papers presented discussing experimental research. From among the many papers submitted, just 49 were selected for publication in this special issue, after peer review by two independent experts These papers cover the topics of: Electrical transport in nano-materials, Optical properties of nano-materials, Magnetic properties of nano-oxide/metallic powders and thin films, Nano-materials with dielectric and ferroelectric properties, Severe plastic deformation to achieve ultra-fine grains, Nano-materials for energy storage applications, Bulk nano-crystalline materials from amorphous ones, Thermal treatment of nano-scale materials, Intermetallic nano-materials by mechanical alloying, Corrosion behaviour of nano-materials, Single- and double-walled carbon nano-tubes, Nano-composites, Quantum dots, Nano-devices and sensors and Biocompatible and biodegradable nano-materials. The book thus fully reflects the current trends in applied nano-materials technology and will be a very useful reference source for any serious student.
"Contains selected peer reviewed papers presented at the International Conference on Nanomaterials and Devices: Processing and Applications (NADPA 2008) held at the Indian Institute of Technology Roorkee, Roorkee 247667, India between December 11-13, 2008"--Preface.
Keywords: Nanostructured materials -- Congresses.; elektronické knihy; electronic books